The rise of the video-recorder teacher: the sociomaterial construction of an educational actor. Issue 8 (16th November 2016) - Perrotta, Carlo; Czerniewicz, Laura; Beetham, Helen
Abstract : This paper draws on actor-network theory and on the sociology of cultural consumption to examine the phenomenon of corporate Massive Open Online Courses. Through an analysis of texts available in the public domain, the paper argues that over a short period (between 2012 and 2013) digitisation technology became associated with the emergence of a hybrid 'actor': the digital video-recorder teacher. A parallel is drawn between the 'interactive affordances' of digital instruction and the playback and cataloguing options that have contributed to shifts in television viewing habits. The digital video-recorder teacher is described as an artefact in the service of a postmodern project of self-improvement through cultural consumption, which recruits digitisation to meet a growing demand for 'upgrades to the self'. In the conclusion, the paper explores how the study of digital education could benefit from an interface between sociomaterial studies and the sociology of culture.